1993
DOI: 10.2105/ajph.83.9.1330
|View full text |Cite
|
Sign up to set email alerts
|

The influence of smoking cessation on body weight may be temporary.

Abstract: The relationships of bodyweight and body mass index with smoking cessation were examined among 1633 adults in Humboldt, Saskatchewan, Canada. Mean body mass index was highest in ex-smokers and lowest in smokers, and that of non-smokers was intermediate. Body mass index decreased significantly with increasing years after smoking cessation in female ex-smokers after adjusting for age, education, location of work, and physical activity. This trend, however, was not significant in men. The body weight data showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 14 publications
(1 reference statement)
1
15
0
Order By: Relevance
“…A recent study has estimated that smoking cessation leads to an average increase of 1.5–1.7 BMI units and that the drop in smoking may explain up to 14 % of the rise in obesity prevalence in recent decades [47]. Weight gain after smoking cessation was less pronounced when number of years since smoking cessation increased [43], and negatively associated with socio-economic status [48]. …”
Section: Discussionmentioning
confidence: 99%
“…A recent study has estimated that smoking cessation leads to an average increase of 1.5–1.7 BMI units and that the drop in smoking may explain up to 14 % of the rise in obesity prevalence in recent decades [47]. Weight gain after smoking cessation was less pronounced when number of years since smoking cessation increased [43], and negatively associated with socio-economic status [48]. …”
Section: Discussionmentioning
confidence: 99%
“…However, most of these studies followed the individuals for only a short period of time. Caan et al (1996) showed that the rate of weight increase after quitting slows after six months, and longer-range studies suggest that some or all of the weight gain is temporary (Mizoue et al, 1998;Chen et al, 1993). Despite the conflicting evidence, fear of weight gain remains a major reason why people postpone quitting smoking, as evidenced by the existence of pills, lozenges, books, internet programs, and even hypnotic techniques that claim to help people quit smoking without gaining weight.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, BMI and obesity status in 1998 are functions of the independent variables in , 1997, 1995, 1994, and 1993. Since 1997and 1995 are not surveyed, I impute the values of the independent variables in those years.…”
Section: Lags Of Cigarette Price/taxmentioning
confidence: 99%
“…'5 Moreover, the inverse relationship between smoking and relative body weight becomes stronger with age,4 which can be explained by longer duration of smoking. 516 Among smokers a U-shaped relationship between the number of cigarettes smoked and relative body weight has been found in several studies-those smoking [10][11][12][13][14][15][16][17][18][19][20] cigarettes per day being the leanest. '5791718 Although this seems paradoxical given the metabolic effects of smoking, it has been suggested that heavy smokers may weigh more because of clustering of other unhealthy habits such as high intake…”
mentioning
confidence: 99%